Upaya mengontrol perilaku agresif pada perilaku Kekerasan dengan pemberian rational emotive behavior therapy - Siregar, Hanna Maria; Gustina, Erita; Pangaribuan, Resmi (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Mental disorders are complex conditions consisting of a variety of problems and symptoms that can cause significant changes in an individual's thinking, emotions and behavior. Aggressive behavior in violent behavior is a mental disorder that can trigger physical danger to oneself and others, accompanied by uncontrolled emotional outbursts, a tendency to display insulting attitudes, be quick to anger and have irrational beliefs. Rational Emotive Behavior Therapy (REBT) is a method for understanding and overcoming emotional and behavioral problems, eliminating illogical thoughts in order to become rational. The main goal of rational emotional behavioral therapy (REBT) is to eliminate emotional disorders that can be self-destructive. This research method uses a descriptive method with a case study, involving 2 patients who experienced problems causing aggressive behavior and violent behavior at the Prof. Mental Hospital. DR. Muhammad Ilrem Medan. The research results of the two respondents while undergoing Rational Emotive Behavior Therapy (REBT) for 3 days with 6 meetings showed that both respondents succeeded in controlling their emotions and reducing violent behavior after being given therapy from SP 1 to SP 5. In conclusion, giving Rational Emotive Behavior Therapy (REBT) can control the patient's emotional violent behavior. It is hoped that this research suggestion can be used as a reference for further research in psychiatric nursing, especially for efforts to control aggressive behavior and violent behavior by providing rational emotive behavior therapy (REBT).